RELATIONSHIP BETWEEN SERVICES QUALITY AND PATIENTS’ SATISFACTION IN OUTPATIENT WARD OF PETALABUMI GENERAL HOSPITAL OF RIAU PROVINCE : RELATIONSHIP BETWEEN SERVICES QUALITY AND PATIENTS’ SATISFACTION (Jurnal kesehatan komunitas (Journal of community health), 2019)
Improving service quality is a top priority in a hospital management. Quality health services could be appeared from five dimensions, namely reliability, responsiveness, assurance, empathy, and tangibles. Excellent patientsâ€™ satisfaction will be obtained if health services applied were in better quality. This research aim was to find out the correlation between service quality with patientsâ€™ satisfaction in outpatient unit of Petala Bumi General Regional Hospital of Riau Province. This was a quantitative study with cross sectional design. Sample were 96 patients which taken by accidental sampling. Data analyzed was bivariate with used Chi Square Test. The result obtained there were correlation reliability ( P value = 0,021, value of OR 3,000), responsiveness ( P value = 0,000, value of OR 5,432), assurance (P value = 0,018, value of OR 3,096), emphaty (P  value = 0,004, value of OR 3,850), tangible ( P value = 0,010, value of OR 3,392) with patientsâ€™ satisfaction in outpatient unit of Petala Bumi GRH of Riau Province. It could be concluded that there was a relationship between service quality and patientsâ€™ satisfaction at the outpatient unit at Petala Bumi GRH of Riau Province. This result suggests to the Petala Bumi GRH on Riau Province to create a strategy and efforts to improve the quality of health services in order to patientsâ€™ satisfaction cloud be increased continually.